Metabolism and Excretion of 8-O-Acetylharpagide in Rats and Identification of Its Potential Anti-Breast Cancer Active Metabolites - Zhao X; Su S; Zhou J; Gao J; Tang X; Wen B (Drug Design, Development and Therapy)
Xinyu Zhao, Sijia Su, Jingna Zhou, Junfeng Gao, Xu Tang, Binyu Wen Dongfang Hospital, Beijing University of Chinese Medicine, Beijing, 100078, People’s Republic of ChinaCorrespondence: Binyu Wen, Dongfang Hospital, Beijing University of Chinese Medicine, Beijing, 100078, People’s Republic of China, Email wen-binyu@163.comBackground: Ajuga decumbens, a traditional Chinese medicine, possesses anti-breast cancer effects. Its main component, 8-O-acetylharpagide, exhibits potential anticancer activity; however, the active metabolites and mechanisms underlying its effects remain unclear.Methods: The metabolism and excretion of 8-O-acetylharpagide in rats were investigated using ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry analysis of bile, urine, and feces. Active metabolites were identified and evaluated using network pharmacology, molecular docking, and Western blotting assays.Results: A total of 21 metabolites were identified, with demethylation, hydrolysis, and glucuronidation being the primary metabolic pathways. M3 and M5 were identified as key metabolites, showing strong binding affinity to cancer-related targets, such as AKT1, MMP9, and STAT3. M5 displayed strong pharmacokinetic properties, including better lipid solubility and reduced polarity. Network pharmacology analysis indicated that these metabolites exert anticancer effects by modulating the PI3K/AKT signaling pathway. In vivo experiments demonstrated that oral administration of 8-O-acetylharpagide significantly inhibited the proliferation of 4T1 tumor tissues by suppressing the expression of the AKT/NF-κB/MMP9 signaling axis. This may be related to inhibition of the expression of the AKT/NF-κB/MMP9 signaling axis in 4T1 tumor tissues after metabolism of 8-O-acetylharpagide to M5 and M3.Conclusion: As a prodrug, 8-O-acetylharpagide is metabolized to M5, which may subsequently exert an anti-breast cancer effect through downregulation of the AKT/NF-κB/MMP9 signaling axis. This study provides a theoretical basis for the clinical application of Ajuga decumbens in breast cancer therapy. Keywords: 8-O-acetylharpagide, breast cancer, ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry, metabolite, network pharmacology, AKT/NF-κB/MMP9 signaling pathway